A new empirical approach to estimate the ratio of horizontal to vertical in-situ stress and evaluation of its effect on the stability analysis of underground spaces (Rudarsko-geološko-naftni zbornik, 2022)
In-situ stress is one of the most important input data to study stability analysis of underground and surface geomechanical projects. The measured vertical stress has a linear relation with depth.  The average value of unit weight () was obtained 0.026 MN/m3 (2.56 ton/m3) using 1041 test results of different rocks with 0.001 difference with 0.027 MN/m3 that is a reliable coefficient for estimating vertical stress.  The ratio of horizontal (h) to vertical (v) stress (Kh/v) is estimated by theoretical and empirical methods. The results showed that the estimating ratio of horizontal to vertical stress (K) by the theoretical method such as Terzaghi and Richard is much smaller than 1, and the estimation of K value utilizing empirical methods such as Hoek and Brady is much greater than 1, and even its value approaches to 4 in the near ground surface.  To overcome the lack of an applicable comprehensive relation for estimation of the K ratio and improve upon the shortcomings of previous methods, a new empirical relation was developed to estimate the K ratio utilizing a significant number of in-situ test results.  Stability analysis of Masjed Soleyman powerhouse caverns was carried out by numerical modelling for five values of K ratio obtained by previous stress estimation methods and this study. The in-situ stress estimation method (K ratio changes) showed a significant effect on stresses, displacements, strains, depth of the plastic zone and significantly affect the stability analysis and support system design of the powerhouse and transformer caverns.